PENGARUH PROMOSI TERHADAP VOLUME PENJUALAN PADA UD. CONSTAN KELURAHAN PASAR TELUK DALAM KABUPATEN NIAS SELATAN - Tarozinduhu Laia (Universitas Nias Raya, 2024)
The objective of this study is to determine the impact of the promotion factor on the Sales Volume factor at UD. Constan located in Telukdalam District, South Nias Regency. This study falls under the category of causal quantitative research. The study methodology used involves the utilisation of basic regression analysis and the management of data using the SPPS (Statistical Product and Service Solutions) 21.0 for Windows software programme. The findings of this study indicate that the tcount value of 1.905 is more than the ttable value of 1.681. Therefore, it can be inferred that the promotion (X) has a statistically significant impact on the sales volume (Y) at UD. Pratiwi Water Telukdalam, with a confidence level of 95%. The analysis yielded a coefficient of determination (R2) of 0.078 (78%), indicating that 78% of the dependent variable can be accounted for by the independent variable, while the remaining 22% is impacted by additional factors not included in this study.